Religion, Religious Heterogeneity, and Intimate Partner Violence Among Korean Immigrant Women - Kim, Chunrye (Journal of interpersonal violence, 2021)
This study examined the role of religious affiliations and frequency of religious service attendance—such as church, Bible studies, and temples—as well as religious heterogeneity between couples on intimate partner violence (IPV) among Korean immigrant women in the United States. Through a case-control design, this study compared 64 Korean immigrant IPV victims with 63 Korean immigrant non-IPV victims. This study’s findings reveal that for Korean immigrant women, a high frequency of religious service attendance was associated with higher IPV victimization, while their partners’ high religious service attendance was associated with lower IPV victimization. When women’s partners were religious compared with when they were not religious, they were less likely to perpetrate IPV even when the partners’ alcohol consumption frequency increased. Also, when there was a gap between couples regarding frequency of religious attendance, IPV victimization increased. This discussion concludes by suggesting some policy implications based on these findings.